Design of website-based Preventive Maintenance Checklist Smart System (PMCSS) to support the operation of ARFF vehicles at I Gusti Ngurah Rai Airport - Bagus Arya Dwipa, I Gusti Ngurah; Abdullah, Anton; Martadinata, M. Indra; Komalasari, Yeti; Amalia, Direstu (Journal of Engineering and Applied Technology, 2024)
This design aims to increase the preparedness of Airport Rescue and Fire Fighting (ARFF) vehicles in supporting operations at I Gusti Ngurah Rai Airport by creating a website-based preventive maintenance application. This research was based on initial observations on the effectiveness level of preventive maintenance systems for operational vehicles that still apply conventional systems so that they are prone to human error. The research and development method was used in this study, including stages namely potential issues, information gathering, product design, product validation, product repair, product trial, and product revision. This study shows that the validation carried out obtained an average percentage of 81.5% with a very decent category. Based on the research results and discussion, it can be concluded that the website-based PMCSS application is effective in supporting ARFF operational vehicles at I Gusti Ngurah Rai Airport.